Overview of Nurse Motivation in Adult Inpatient Room - Liestyaningrum, Wiwiek; Saribu, Hotmaria Julia Dolok; Sari, Komala (STIKep PPNI Jawa Barat, 2024)
Aims: to determine the description of the level of nurse motivation in the inpatient ward of Dabo Regional Hospital. Method: This study used a descriptive design with a total sampling of 44 nurses in the adult inpatient ward of Dabo Regional Hospital. Data were collected through a nurse motivation questionnaire consisting of 13 statements and analyzed using a frequency distribution. Results: The results showed that 59.09% of nurses experienced low motivation, while 40.91% had high motivation. Demographic characteristics, such as age, gender, education, and length of service, influenced the level of motivation. Discussion: Factors that influence nurse motivation include the work environment, management support, and reward systems. An unsupportive work environment and lack of appreciation from management contributed to this problem. Conclusion: This study concludes that there is an urgent need to improve nurses' motivation at Dabo Regional Hospital through effective managerial strategies. Recommendations for further research are to determine the factors that influence nurses' work stress in adult inpatient wards.